Numerical experiments with p F- and q D-strings: the formation of (p,q) bound states - Rajantie,A; Sakellariadou,M; Stoica,H (Journal of Cosmology and Astroparticle Physics, 2007)
We investigate the behaviour of (p, q) string networks, focusing on two aspects: (1) modelling more realistic (p, q) string networks than the ZN networks used so far, and (2) investigating the effect of long-range interactions on the evolution of the network. We model the network with no long-range interactions using two sets of fields, complex scalars coupled to gauge fields, with a potential chosen such that the two types of strings will form bound states. This way we can model junctions of three strings with different tension; in ZN models used so far in simulations all the strings have identical tensions. In order to introduce long-range interactions we also study a network in which one of the scalars forms global strings. We observe that in the absence of long-range interactions the formation of bound states has a significant influence on the evolution of the network. When long-range interactions are turned on, the bound states are short-lived and have a minimal effect on the network evolution.